PENGARUH PENERAPAN MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA SUBTEMA PELESTARIAN KEKAYAAN SUMBER DAYA ALAM DI INDONESIA: Pendekatan Penelitian Eksperimen Kuasi di Kelas IV Sekolah Dasar Negeri Ciapus 01 Kabupaten Bogor Semester Genap Tahun Ajaran 2021/2022 - Anasis Derati Meilatalimi; Tatang Muhajang; Nita Karmila (STKIP Subang, 2022)
This study aims to determine the effect of applying the Project Based Learning model to the learning outcomes of fourth grade students on theme 9 Kayanya Negeriku, subtheme 3 Preservation of Natural Resource Wealth in Indonesia. This type of research is quantitative in the form of a quasi-experimental design with two groups. This research was conducted at Ciapus 01 Public Elementary School, Ciomas District, Bogor Regency. The research population was all students of grades IV A and IV B of Ciapus 01 Public Elementary School, totaling 61 students. The research was conducted in the even semester of the 2021/2022 academic year. The results showed that there was an effect of applying the Project Based Learning model to student learning outcomes in subtheme 3 of preserving natural resource wealth in Indonesia. This can be seen from the N-Gain value in the experimental class group of 67, while in the control group it is 44. As well as the results of testing the hypothesis that H0 is rejected and Ha is accepted because tcount (4.71) > ttable (2.01). Thus it can be concluded that the application of the Project Based Learning model has a positive influence on the learning outcomes of subtheme 3 preservation of natural resource wealth in Indonesia.